PENGARUH PENERAPAN WAREHOUSE MANAGEMENT SYSTEM (WMS) SEBELUM DAN SESUDAH TERHADAP KINERJA KARYAWAN GUDANG FINISH GOOD PADA PT. TRITEGUH MANUNGGAL SEJATI GOWA - Ahmad Padhil; Asih Setyo Rini; Aurah Musdalifah Husni (LPPM Universitas Bina Bangsa, 2023)
Warehouse is a means of storing stock of goods in a supply chain (Supplychain). The management system in warehousing requires a database-based computer application system, which is used to improve warehouse efficiency in maintaining the accuracy of inventory data by recording every transaction in the warehouse, setting goods storage methods, and integration between warehouses. All of these aspects must be regulated properly, because if not, decreased warehouse performance can lead to a loss in the supply chain. PT. Triteguh Manunggal Sejati-Gowa is one of the companies engaged in the soft drink industry by producing and supplying soft drinks in the Eastern Indonesia region, precisely on Jl. Axis Malino KM. 21, Pakatto Village, Bontomarannu District, Gowa Regency, South Sulawesi-Indonesia. In this study only to identify how the quality of warehouse employee performance at PT.Triteguh Manunggal Sejati Gowa and how the influence before and after the implementation of the Warehouse Management System (WMS). This study aims to determine how the quality of warehouse performance at PT.Triteguh Manunggal Sejati Gowa and Knowing the effect before and after the implementation of the Warehouse Management System (WMS) on the performance of the warehouse at PT.Triteguh Manuggal Sejati Gowa. by using multiple linear regression method. And the results of this study show that the quality of the performance of Finish Good warehouse employees has good quality after the implementation of the warehouse management system. It can be seen from the increase in performance effectiveness. and the results of further research on the influence before and after the implementation of WMS on warehouse performance there is a simultaneous influence on the performance of warehouse employees finish good can be seen from F count greater than F table that is 14,327 greater than 4.46 and a significance level of 0.003 less than 0.05